Mappings by the complex exponential function. (December 2020) - Triana, J G; Fuentes, J A; Ramirez, P
Abstract: In mathematics, engineering, and physics, some problems can be solved through complex functions; in many cases, with geometric inconveniences or complicated domains. Conformal mappings are essential to transform a complicated analytic domain onto a simple domain. Physical approaches to visualization of complex functions can be used to represent conformal mappings, here we use the transformation of regions of the complex plane. This paper provides a graphical overview of the transformation of a set of regions by the complex exponential function.